A critical review on mechanical and morphological characteristics of injection molded biodegradable composites. Issue 12 (6th October 2022) - Gorrepotu, Surya Rao; Debnath, Kishore; Mahapatra, Rabindra Narayan; Srivatsan, Tirumalai S.
Abstract: Factors like environmental and societal awareness often lead to a significant change of action in the development of eco‐friendly materials like the family of green composites. Green composites are becoming increasingly apparent as a sensible and potentially viable alternative to the synthetic composites. A healthy synergism of factors to include weight reduction, cost, performance improvement, biodegradable nature, nontoxic properties, and flexibility are often the key motives that provide the much needed impetus for the development of green composites for the purpose of selection and use in a spectrum of applications. The biodegradable or green composites became a viable substitute for the long‐established materials and often a challenge to the family of synthetic polymer‐based composites. The present study draws attention to the issues and challenges that come in the way of development and characterization of "green" composites primarily on the use of advanced manufacturing processes like injection molding. In this article, the chemical composition, structure, mechanical properties, and classification of the natural fibers are presented and briefly discussed. The mechanical properties, to include tensile response, flexural behavior, and impact strength, of the injection molded composites are presented and adequately discussed. The effect and role of surface treatments and coupling agents on mechanical properties of the family of polymer composites, to include the nonbiodegradable composites, partially green composites, and fully green composites, are examined and adequately discussed. Abstract :